2023
DOI: 10.3390/jcm12020652
|View full text |Cite
|
Sign up to set email alerts
|

Craniofacial Morphology of Temporomandibular Disorder Patients with Different Disc Positions: Stratifying Features Based on Sex and Sagittal Skeletal Pattern

Abstract: Disc displacement (DD) appears in the majority of temporomandibular disorder (TMD) patients. The correlation between craniofacial morphology and different disc positions has been underlined, while the craniofacial morphological differences based on sex and sagittal skeletal pattern stratification have been insufficiently studied. In this study, 304 patients with TMD complaints were included and classified into normal position, disc displacement with reduction (DDwR) and disc displacement without reduction (DDw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…study. These data are also in agreement with other authors who confirmed the age range of diagnosis of RDC/TMD and that the prevalence of TMD in women is higher, due to hormonal factors, arch size, use of prostheses and socioeconomic conditions (Mesquita, et al, 2022;Bueno, et al, 2018;Ye, et al, 2023;Ferreira, et al, 2016;Bonini, et al, 2014;Janal, et al, 2008). Research, Society and Development, v. 12, n. 5, e17812541593, 2023 (CC BY 4.0) Source: Authors (2023).…”
Section: Resultssupporting
confidence: 93%
“…study. These data are also in agreement with other authors who confirmed the age range of diagnosis of RDC/TMD and that the prevalence of TMD in women is higher, due to hormonal factors, arch size, use of prostheses and socioeconomic conditions (Mesquita, et al, 2022;Bueno, et al, 2018;Ye, et al, 2023;Ferreira, et al, 2016;Bonini, et al, 2014;Janal, et al, 2008). Research, Society and Development, v. 12, n. 5, e17812541593, 2023 (CC BY 4.0) Source: Authors (2023).…”
Section: Resultssupporting
confidence: 93%
“…Individuals with TMDs may exhibit different disc positions, leading to changes in craniofacial morphologies and potential effects on mandibular growth and dentofacial structure. 25,26 At the same time, condylar shape alteration resulting from CE can also contribute to maxillofacial developmental deformities. 22 Despite this, the impact of specific DD types on the severity of CE, as well as the potential effects of DD on craniofacial morphology, remains unclear.…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…Previous studies have investigated the relationship between DD and DJD, 23,24 but there is limited research exists on how DD type affects the severity of CE. Individuals with TMDs may exhibit different disc positions, leading to changes in craniofacial morphologies and potential effects on mandibular growth and dentofacial structure 25,26 . At the same time, condylar shape alteration resulting from CE can also contribute to maxillofacial developmental deformities 22 .…”
Section: Introductionmentioning
confidence: 99%